2022
DOI: 10.31557/apjcp.2022.23.12.4233
|View full text |Cite
|
Sign up to set email alerts
|

A Dosimetric and Radiobiological Comparison of Intensity Modulated Radiotherapy, Volumetric Modulated Arc Therapy and Helical Tomotherapy Planning Techniques in Synchronous Bilateral Breast Cancer

Abstract: Objective: The present investigation intends to identify the optimal radiotherapy treatment plan for synchronous bilateral breast cancer (SBBC) using dosimetric and radiobiological indexes for three techniques, namely, helical tomotherapy (HT), volumetric modulated arc therapy (VMAT), and intensity-modulated radiotherapy (IMRT). Methods: Twenty SBBC treated female patients treatment planning data (average age of 52.5 years) were used as the sample for the present study. Three different plans were created using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…We have studied the possibility of sparing the hippocampus and other OARs while performing the WBRT and simultaneous boost with the three planning methods and compare these plans with dosimetric, EUD, and radiobiological models. Balasubramanian et al [22,23] compared photon and proton planning radiobiologically using LKB and Niemierko NTCP models, and they found that the results were reliable for comparing different planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…We have studied the possibility of sparing the hippocampus and other OARs while performing the WBRT and simultaneous boost with the three planning methods and compare these plans with dosimetric, EUD, and radiobiological models. Balasubramanian et al [22,23] compared photon and proton planning radiobiologically using LKB and Niemierko NTCP models, and they found that the results were reliable for comparing different planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…We have studied the possibility of sparing the hippocampus and other OARs while performing the WBRT and simultaneous boost with the three planning methods and compare these plans with dosimetric, EUD, and radiobiological models. Balasubramanian et al [22,23] compared photon and proton planning radiobiologically using LKB and Niemierko NTCP models, and they found that the results were reliable for comparing different planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies include all relevant OARs and/or substructures of the heart [28] . Some studies incorporate NTCP models in the treatment technique planning comparison, but for other treatment sites [29] , [30] , [31] . It is important to evaluate the current treatment planning techniques by including these new insights.…”
Section: Introductionmentioning
confidence: 99%